ANALISIS JALUR FAKTOR-FAKTOR YANG MEMENGARUHI RISIKO TERKENA PENYAKIT DIABETES MELITUS - TEO, DOMINGGAS; SUKARSA, I KOMANG GDE; SRINADI, I GUSTI AYU MADE; KENCANA, I PUTU EKA NILA (E-Jurnal Matematika; Vol 11 No 1 (2022), 2022)
Diabetes mellitus is a non-contagious disease that causes the increas of death rates in Indonesia. This study aims to determine the causality between Age, Occupation, Cholesterol effects of Age, Occupation, Cholesterol Levels, and Blood Pressure Risk of Diabetes Mellitus (DM). The population in this study were all patients at the Beru Public Health Center, with a sample of 200 patients. The analytical method used in this research is Path Analysis with the help of directly or indirectly. The results showed that age and blood pressure had a direct positive effect on cholesterol levels and blood pressure, and age, cholesterol levels and blood pressure also directly affected the risk of developing DM. Age and occupation also affect the risk of developing DM indirectly.